PENGARUH CELEBRITY ENDORSE DAN BRAND TRUST TERHADAP KEPUTUSAN MEMBELI: studi deskriptif kuantitatif tentang pengaruh celebrity endorse dan brand trust "kaesang pangarep" terhadap keputusan membeli di cafe hebat solo - Pradana Sakti, Dimas Bernanda; Wangi, Maya Sekar; Hindra H, Nurnawati (Solidaritas, 2024)
Marketing strategies have evolved along with technological advances and changing consumer behavior. The use of celebrities as endorsers is increasingly common in promoting products to increase consumer appeal and trust in the brand. Cafe Hebat Solo, as a culinary business, implements this strategy by using Kaesang Pangarep as an endorser, so it is necessary to analyze its influence on consumer purchasing decisions. Purchasing decisions are a process carried out by consumers to fulfill their needs in order to obtain satisfaction with the highest value. Consumer decision-making to purchase a product begins with an awareness of the fulfillment of needs and desires. The purpose of this study is to analyze the influence of Celebrity Endorsement and Brand Trust on purchasing decisions at Cafe Hebat Solo. The theory used in this study is the Brand Trust theory. Consumer trust in a brand can strengthen purchasing decisions, and Celebrity Endorsement The use of celebrities in marketing aims to increase consumer trust and interest in the product. This study uses a quantitative approach with a survey method. The research sample consisted of 96 respondents who were customers of Cafe Hebat Solo. Data were collected through a questionnaire with questions that measured the influence of celebrity endorsers and brand trust on purchasing decisions. The analysis was carried out using multiple linear regression to test the relationship between independent variables. The results of the study indicate that both celebrity endorsement and brand trust have a significant influence on purchasing decisions. The T-test conducted shows that the Celebrity Endorsement variable has a t-value of 20,641 with a significant value of 0.000, which means its influence is significant. The Brand Trust variable has a t-value of 2,878 with a significant value of 0.005, also indicating a significant influence. Simultaneously, celebrity endorsement and brand trust contribute significantly to purchasing decisions, with an adjusted R-square of 0.851 or 85%, which means that these two variables explain 85% of the variability in consumer purchasing decisions at Cafe Hebat. Keywords: Celebrity Endorsement, Brand Trust, Purchase Decision